(untitled) (Research, Society and Development, 2021)
This article aims to highlight the usability of the IRaMuTeq software, analyzing and comparing the TCC, summaries of the students of the Professional Master in Professional and Technological Education - ProfEPT, available on the Sucupira Platform in December 2019 with the bibliography indicated in the access exams to the Program. The use of the IRaMuTeq software proves to be an important tool for organizing data for conducting content analysis, proposed by Bardin (1977), as it allows several organizations of the analyzed content, among them those of the Lexographic, Specificities, Factor Analysis Correspondence (AFC), Descending Hierarchical Classification Method (CHD), Similitude Analysis and Word Cloud. The application of the IRaMuTeQ software made it possible to perform these analyzes more quickly and demonstrated that there is a consonance between the terms used by ProfEPT students in their TCCs and the theoretical references of the program. The software proved to be quite useful, especially in phase two of the content analysis technique, proposed by Bardin (1977), however, to fully apply this technique, the role of the researcher in phase three is essential, when discussing and interpreting the results demonstrated by the free software IRaMuTeq.